Determinasi Keputusan Pembelian: Analisis Inovasi dan Desain Produk - Nyoman Dwika Ayu Amrita; I Komang Yoga Narayana (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2023)
Endek woven fabric is one of the traditional fabrics of Balinese cultural heritage that is still preserved. Endek woven fabrics are known for their beautiful motifs, color combinations and the fineness of the fabric fibers. Endek woven fabrics already have their own consumers and consumeripurchasing decisionsiare very importantito beiconsiderediby craftsmen. Thisistudy aims toiidetermine theiiiinfluence of innovationi and productiiidesign on consumer purchasingidecisions on Riski Adijaya endek woven fabrics Product in Sidemen sub-District of Karangasem. Thisiresearch wasiconducted inione ofithe weaving businesses in Sidemen District. The object of this research is innovation (X1), product design (X2) and purchasing decisions (Y). The number of samples taken is one hundred respondents using accidental sampling technique. Dataicollection techniquesiused areiobservation, interviewsiand questionnaires. Theidata analysisitechnique usediis validityitest, reliabilityitest, classical assumptionitest, multipleilinear regressionianalysis, analysis ofidetermination, Fitesti (F-test) andit-testi (t-test). The results of this studyiindicate that innovation and productidesign have a positive and significant effect both simultaneously and partially on consumeripurchasing decisions on Riski Adijaya endek woven fabrics Product in Sidemen sub-District of Karangasem. Whichimeans thatithe better the innovationiand product designiused, the higher the consumer'sidesire to make aipurchase.